MUSLIMPRENEURSHIP IN INDONESIA'S DIGITAL ERA: OPPORTUNITIES, CHALLENGES, AND STRATEGIES FOR DEVELOPING ISLAMIC VALUE-BASED BUSINESSES - Rizqon Halal Syah Aji; Havis Aravik; Ahmad Tohir (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
The development of global digitalization has driven a major transformation in the Sharia-based entrepreneurship sector through the emergence of Muslimpreneurship as a modern business model that integrates digital technology with Islamic values. However, this development has also presented various problems such as low digital Sharia literacy, cybersecurity threats, weak Sharia compliance in digital transactions, and limited human resources competent in technology and Islamic economics. This study aims to analyze the opportunities, challenges, and strategies for developing Islamic values-based Muslimpreneurship in Indonesia's digital era. The study used a qualitative method with a library research approach. Data were obtained from books, scientific journals, proceedings, regulations, and various trusted publications relevant to Sharia economics, digital entrepreneurship, Sharia fintech, and the halal industry. Data analysis was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results show that digitalization offers significant opportunities for Muslimpreneurs through the development of halal e-commerce, Sharia fintech, digital marketing, and global market expansion. However, challenges related to digital security, Sharia literacy, and human resource competency remain major obstacles. This research contributes to the development of digital Sharia economic studies by offering strategies to strengthen Muslimpreneurship based on the values of shidiq, amanah, tabligh, and fathonah to create ethical, competitive, and sustainable digital businesses.